2013
DOI: 10.11564/20-2-393
|View full text |Cite
|
Sign up to set email alerts
|

Fertility Differentials in Kenya: The Effect of Female Migration

Abstract: This study uses the Kenya Demographic and Health Survey (KDHS)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 12 publications
0
6
0
Order By: Relevance
“…Lower fertility among urban migrants compared to non-migrants in the places of origin has been found in much of the recent literature on SSA (Brockerhoff 1998 ; Omondi and Ayiemba 2005 ; White, Muhidin, et al 2008 ; White et al 2005 ). This is also closely aligned with recent studies from West Africa on internal migration to a capital city, which also found remarkably similar fertility outcomes between migrants and non-migrants in Accra, Ghana (Rokicki, Montana, and Fink 2014 ).…”
Section: Discussionmentioning
confidence: 84%
See 2 more Smart Citations
“…Lower fertility among urban migrants compared to non-migrants in the places of origin has been found in much of the recent literature on SSA (Brockerhoff 1998 ; Omondi and Ayiemba 2005 ; White, Muhidin, et al 2008 ; White et al 2005 ). This is also closely aligned with recent studies from West Africa on internal migration to a capital city, which also found remarkably similar fertility outcomes between migrants and non-migrants in Accra, Ghana (Rokicki, Montana, and Fink 2014 ).…”
Section: Discussionmentioning
confidence: 84%
“…The limited existing research on this topic has found mixed results. Most cross-sectional studies have found that migration to urban areas is associated with lower fertility (Brockerhoff 1995 ; Brockerhoff 1998 ; Omondi and Ayiemba 2005 ), both for migrants themselves (Brockerhoff and Yang 1994 ) and for subsequent generations born in the urban place of destination (White et al 2005 ). Similarly, two recent longitudinal studies of migration and fertility in Ghana found lower fertility among rural-to-urban migrants (Chattopadhyay, White, Debpuur, et al 2006 ; White, Muhidin, et al 2008 ) compared to rural non-residents.…”
Section: Backgroudmentioning
confidence: 99%
See 1 more Smart Citation
“…The selectivity hypothesis suffices in describing the fertility patterns of the Igbo migrants in the North-West and Hausa-Fulani migrants in the South-East as evidence shows that the socioeconomic characteristics of both sets of migrants differed from those of the stayers' population in their home regions and those of the destination population. Reason for migration and other social and economic aspirations of the migrants may be responsible for the difference as have been shown by Omondi and Ayiemba (2005) in Kenya. Although at bivariate levels and the multivariate level of all migrants, there exist significant associations and relationships between fertility behavior and the sociodemographic covariates investigated in this study, the relationships assumed an ethnic dimension at the level of individual ethnic group.…”
Section: Discussionmentioning
confidence: 89%
“…Omoyeni (2013) also reported lower fertility among migrants. Omondi and Ayiemba (2005) had attributed such pattern in Kenya to female migrants' relegation of their reproductive roles for self-actualization activities like career development.…”
Section: Introductionmentioning
confidence: 99%